Louisiana Medicaid Expansion and Pent-Up Demand. Issue 11 (26th November 2022) - Walker, Brigham; Zhou, Danju; Callison, Kevin
Abstract : Background: Nearly half a million newly eligible people enrolled in Louisiana Medicaid following its expansion. Objectives: To evaluate postexpansion utilization trends in Louisiana Medicaid. Research Design: We plotted utilization trends for expansion and traditional Medicaid beneficiaries and conducted regression analyses to evaluate differences in monthly trends for over 2 years following expansion. Subjects: We restricted our sample to a balanced panel of beneficiaries aged 18–64. The expansion population included beneficiaries who enrolled in the first month of eligibility. The nonexpansion group enrolled at least a year pre-expansion. Measures: Monthly office visits, emergency department visits, and inpatient stays per 1000 enrollees, drawn from the Louisiana Medicaid Data Warehouse claims database. Results: Compared with trends among traditional Medicaid beneficiaries, expansion beneficiaries utilized 4.59 [ P =0.08] more monthly office visits per 1000 enrollees in their first year, increasing to 6.33 [ P <0.01] more per month thereafter. Monthly emergency department visit trends were not statistically significantly different in the first year but were 0.71 [ P <0.01] monthly visits lower for expansion beneficiaries thereafter. Trends in monthly inpatient stays were 0.23 [ P =0.02] stays per 1000 enrollees higher in the first year for expansion beneficiaries but were not statistically significantly different thereafter. Conclusions: Louisiana Medicaid expansion beneficiaries experienced lower initial rates of office visits compared with traditional Medicaid beneficiaries, but these rates consistently increased over the first 2 years after expansion. The expansion population had uniformly higher levels of emergency department and inpatient visits throughout the study period. After the first postexpansion year, emergency department visits among expansion beneficiaries fell relative to traditional beneficiaries while inpatient utilization trends leveled off after an initial increase.